Characteristics of charge/discharge and alternating current impedance in all-vanadium redox flow batteries. (1st February 2019) - Sun, Hong; Yu, Mingfu; Li, Qiang; Zhuang, Kaiming; Li, Jie; Almheiri, Saif; Zhang, Xiaochen
Abstract: Although all-vanadium redox flow batteries (VRB) are potentially suitable for large-scale energy storage, their low energy density, their limited operating temperature, and the development of electrolyte imbalances over time limit their applications. Addressing these limitations will require the development of methods for systematically assessing factors, such as the operating parameters, that affect VRB performance. In this study, a flow battery test system was developed and used to assess the charge/discharge characteristics and alternating current (AC) impedance of a single-cell all-vanadium redox flow battery. Equivalent circuits and equivalent resistance elements were investigated by means of the equivalent circuit method combined with AC impedance spectroscopy. The effects of current density, electrolyte solution flow rate, and vanadium ion concentration on the charge/discharge characteristics and AC impedance of the battery were analyzed, as was the influence of over-charge on ohmic impedance. The results indicated that the equivalent resistance elements of the battery consisted of ohmic resistance, faraday resistances, and capacitances; the faraday resistance in the positive electrode was greater than that in the negative electrode. Increasing the vanadium ion concentration increased the ohmic resistance and the faraday resistances, particularly the faraday resistance in the positive electrode. The impedance of VRB can be effectively control by proper using of the equivalent circuit.